PENGARUH FAKTOR-FAKTOR KEPEMIMPINAN SKW TERHADAP MOTIVASI PETANI DALAM MELAKSANAKAN PROGRAM PENGEMBANGAN TEBU RAKYAT (Studi pada Tani Tebu Rakyat di Wilayah Kab. Sidoarjo Binaan PG. Kremboong) - Heppy Cahyaning Windo (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This researchaims to identify and analyzen the influence factors of leadership comprising plan, supervision, coaching, invitation and communication the motivation of farmers in the development of sugarcane in PG.Kremboong Sidoarjo. Bases Model Summary analysis regression elaboration of multiple linear regression obtainable value R Multiple of 0,811, means indicates a very strong relationship, while the results R Square 0,658 means the influence of variable factors motivational leadership to sugarcane farmers can be explained by the regression model for 65,8% while the remaining 34,2% influenced by other variables not examined. While standars error of the estimate is 0,30071. Mean standard error rate is only 0,30071. This shows that the level of accuracy of the results of the study are representative. Variable most dominant influence on sugar cane farmer motivation is coaching, as indicated by the beta coefficient (????) of 0,392 or influenced by 39,2% compared to the other variabel in a row is an invition (X4) 0,280, supervision (X5) 0,157 , communication (X2) 0,123, and plan (X1) 0,072.